Quick, but Not Dirty: The Usefulness of Flash Mob Studies as a Method for Action Research in eHealth - Kira Oberschmidt; Christiane Grünloh; Stephanie Jansen-Kosterink; Monique Tabak (Journal of Participatory Research Methods)
Action research (AR) is a participatory research approach that works in iterative cycles that are conducted in practice. However, some cycles of AR can take a long time, slowing down the speed of iterations. Therefore, in this study we investigate the use of a relatively new method for AR: the flash mob. Flash mob studies lend themselves to spontaneous, unplanned participation, by collecting large amounts of data in a short time, while also analyzing and reporting quickly on findings. To investigate the applicability of the flash mob as a method for AR in eHealth projects, we conducted three flash mob studies in two research projects and drew recommendations based on observations, reflections and short pre- and post-surveys. Outcomes show that the flash mob is a potential method for AR, as it is situated in a practical setting where stakeholders can easily be involved, and its pace could speed up the AR cycles. To further improve the applicability for AR, our main recommendations include: promoting the flash mob adequately to increase participation and improve the involvement of 'champions'; tracking interactions outside the flash mob (e.g., comments and questions from bystanders); and choosing an accessible and visible location, taking into account the activities associated with the location.